Analisis Pengendalian Kualitas Produk untuk Meminimumkan Produk Gagal Pada Pabrik Roti Prabu Bakery - Nia Friscilla; Achmad Syamsudin; Deddy Rakhmad Hidayat (Fakultas Ekonomi Dan Bisnis Universitas Palangka Raya (UPR), 2021)
Operations and management research are areas of interest in the SMEs production house. Production process control and quality control in the operational system are implemented to keep the product good and acceptable according to customer requirements. The research target at the Prabu Bread Production House in Palangka Raya City, Central Kalimantan is to provide operational education with a flow chart in reducing failed products. Resource theory in research is the basis for managing production and product operations effectively and efficiently. This type of research is observation and interviews with time system analysis with diagrams as quality control ranging from material selection to packaging. Based on the results of the flow chart and time structure in each production step, it is very good at supporting products to reduce production failures. Practical research implications are expected to provide knowledge in society, especially in the field of operations, especially product quality control to minimize failed products. Thus, bakery products produced by producers can be guaranteed quality is accepted by consumers and failed products produced by producers can be reduced or no longer exist.